Vibrio cholerae as a predator: lessons from evolutionary principles - Pukatzki, Stefan; Provenzano, Daniele (Frontiers in Microbiology, 2013)
Diarrheal diseases are the second-most common cause of death among children under the age of five worldwide. Cholera alone, caused by the marine bacterium Vibrio cholerae, is responsible for several million cases and over 120,000 deaths annually. When contaminated water is ingested, V. cholerae passes through the gastric acid barrier, penetrates the mucin layer of the small intestine, and adheres to the underlying epithelial lining. V. cholerae multiplies rapidly, secretes cholera toxin, and exits the human host in vast numbers during diarrheal purges. How V. cholerae rapidly reaches such high numbers during each purge is not clearly understood. We propose that V. cholerae employs its bactericidal type VI secretion system to engage in intraspecies and intraguild predation for nutrient acquisition to support rapid growth and multiplication.